Principal influence in teacher hiring: documenting decentralization over time. Issue 3 (9th May 2018) - Engel, Mimi; Cannata, Marisa; Curran, F. Chris
Abstract : Purpose: Over the past decade, policy researchers and advocates have called for the decentralization of teacher hiring decisions from district offices to school principals. The purpose of this paper is to document the trends across two and a half decades in principals' reported influence over teacher hiring decisions in the USA and explore how and whether principal influence varies systematically across contexts. Design/methodology/approach: Regression analysis with secondary data using seven waves of nationally representative data from the Schools and Staffing Survey. Findings: Principals report increased influence over the 25 years that the data span. While principals of urban schools were much more likely to report having less influence over teacher hiring compared to their non-urban counterparts in the late 1980s and early 1990s, their reported influence increased more than that of other principals. Research limitations/implications: Empowering principals as primary decision-makers assumes that they have the best information on which to make hiring decisions. At the same time, other research suggests that local teacher labor market dynamics contribute to the inequitable sorting of teachers across schools. This study raises questions regarding the implications of the increased influence of principals in teacher hiring on equity of access to quality teachers across schools. Originality/value: This is the first study to explore whether and how principal influence in teacher hiring decisions has changed over time.